Higher-spin states of the superstring in an electromagnetic background - Benakli, Karim; Berkovits, Nathan [UNESP]; Daniel, Cassiano A. [UNESP]; Lize, Matheus [UNESP] (Springer Nature, 2021)
Constructing a consistent four-dimensional Lagrangian for charged massive higher-spin fields propagating in an electromagnetic background is an open problem. In 1989, Argyres and Nappi used bosonic open string field theory to construct a Lagrangian for charged massive spin-2 fields in a constant electromagnetic background. In this paper, we use the four-dimensional hybrid formalism for open superstring field theory to construct a supersymmetric Lagrangian for charged massive spin-2 and spin-3/2 fields in a constant electromagnetic background. The hybrid formalism has the advantage over the RNS formalism of manifest N = 1 d=4 spacetime supersymmetry so that the spin-2 and spin-3/2 fields are combined into a single superfield and there is no need for picture-changing or spin fields.
Keywords: String Field Theory; Supersymmetric Effective Theories